2020
DOI: 10.1186/s13019-020-01244-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of concomitant tricuspid valve repair in patients undergoing mitral valve surgery

Abstract: Background We aimed to find out how the concomitant performance of tricuspid valve repair (TVR) affects outcomes of patients undergoing mitral valve surgery (MVS). Methods Single-centre, retrospective analysis of 1357 patients who underwent MVS between January 2005 and December 2015, including 1165 patients with isolated MVS and 192 patients with MVS plus TVR. We used propensity scores to match patients for baseline characteristics other than valve related parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…23 Several studies found improved outcomes after repairing moderate or less degree TR concomitant with MV surgery. 16,24,25 The progression of postoperative TR was proportional to the preoperative TR grade.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several studies found improved outcomes after repairing moderate or less degree TR concomitant with MV surgery. 16,24,25 The progression of postoperative TR was proportional to the preoperative TR grade.…”
Section: Discussionmentioning
confidence: 99%
“…After matching no difference in 30-day and 120-day mortality were found and the postoperative complication rates were similar between the groups. The median length of hospital stay was longer in the MIDVS group (9 days [6][7][8][9][10][11][12][13] vs. 7 days [6][7][8][9][10][11]; p = .04) in the SDV group. (Table 4) Kaplan-Meier analyses in the matched population showed no significant difference between MIDVS and SDV (94.7% vs. 93.3%, Log-Rank p = .62 Figure 1B).…”
Section: Minimally Invasive Double Valve Surgery Compared To Sternoto...mentioning
confidence: 99%
“…No differences in 30-day mortality (n = 0 [0] vs. n = 5 [0.7]; p = .99) and 120-day mortality (n = 1 [1.2] vs. n = 7 [1.0]; p = .99) were observed (Table S1). A longer median hospital stay (9 days [6][7][8][9][10][11][12][13] vs. 6 days [5][6][7][8]; p < .001), a higher incidence of new onset arrythmia (n = 39 [45.3] vs. n = 134 [19.4]; p < .001) and higher need for re-exploration of bleeding (n = 12 [14.0] vs. n = 30 [4.4]; p = .001) was observed for MIDVS in the unmatched population compared with MIMVS (see Table S1).…”
Section: Minimally Invasive Double Valve Surgery Compared To Minimall...mentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant tricuspid valve disease is not uncommon. Mitral and/or tricuspid intervention may entail increased procedural complexities 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%